MENINGKATKAN KEMAMPUAN MEMBACA KATA MELALUI PEMBELAJARAN AKTIF, INOVATIF, KREATIF, EFEKTIF DAN MENYENANGKAN BAGI ANAK TUNAGRAHITA RINGAN KELAS III DI SLB MUHAMMADIYAH PAUH IX PADANG - Nadia Murni, Martias, Z, Rahmatrisilvi (Jurnal Penelitian Pendidikan Khusus, 2013)
The research was backgrounded  by the problem of  that researcher found in ability of reading word with retardation mental needs in class III of  junior high school special of  school of Muhammadiyah Pauh IX Padang. The researcher want to prove that ability  that the use of study aktive,innovative,creative,effective and fun can improve the ability in reading of child with retardation mental need. This research using single subject research approach the A-B-A design and data analysis techniques using visual analysis chart. Results of this study indicate that the study aktive, innovative, creative, effective and fun has improved the ability in reading of  child with retardation mental in class III of junior high of  special school of Muhammadiyah Pauh IX Padang